How do our ears hear? - Ballard, Carol (Austin, Tex. : Raintree Steck-Vaughn, 1998)
Introduces the parts of the ear and explains how they help us hear sounds.
Includes bibliographical references and index.
Keywords: Hearing -- Juvenile literature; Ear -- Juvenile literature; Hearing; Ear; Senses and sensation